The roles of secreted wnt ligands in cancer - Werner, Johannes; Boonekamp, Kim E.; Zhan, Tianzuo; Boutros, Michael (International journal of molecular sciences, 2023)
Wnt ligands are secreted signaling proteins that display a wide range of biological effects. They play key roles in stimulating Wnt signaling pathways to facilitate processes such as tissue homeostasis and regeneration. Dysregulation of Wnt signaling is a hallmark of many cancers and genetic alterations in various Wnt signaling components, which result in ligand-independent or ligand-dependent hyperactivation of the pathway that have been identified. Recently, research is focusing on the impact of Wnt signaling on the interaction between tumor cells and their micro-environment. This Wnt-mediated crosstalk can act either in a tumor promoting or suppressing fashion. In this review, we comprehensively outline the function of Wnt ligands in different tumor entities and their impact on key phenotypes, including cancer stemness, drug resistance, metastasis, and immune evasion. Lastly, we elaborate approaches to target Wnt ligands in cancer therapy.
Gesehen am 25.05.2025